Pengaruh Citra Merek, Harga dan Kualitas Produk Terhadap Minat Beli Pada Miniso Kota Parepare - Mariana, Mariana; Umaima, Umaima (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study aims to analyze the effect of brand image, price, and product quality on consumer purchase intention at Miniso in Parepare City. Using a quantitative approach, the research collects data through a survey involving 96 respondents who are consumers of Miniso in Parepare City. Data analysis is conducted using multiple regression analysis techniques. The results show that brand image does not have a significant effect on purchase intention for Miniso products in Parepare City, price has a significant effect on purchase intention for Miniso products in Parepare City, and product quality has a significant effect on purchase intention for Miniso products in Parepare City.